1991
DOI: 10.1073/pnas.88.18.8052
|View full text |Cite
|
Sign up to set email alerts
|

The initiator directs the assembly of a transcription factor IID-dependent transcription complex.

Abstract: Highly purified RNA polymerase H was found to be able to weakly recognize the initiator (Inr) present in the adenovirus IVa2 and major late promoters. The association of RNA polymerase H with the Inr was enhanced by the general transcription factors. The Inr was capable of directing the formation of a DNA-protein complex. Transcription competent complexes on the adenovirus major late and IVa2 promoters appear to be formed by alternative pathways mediated through the Inr and/or "TATA" motif. The presence of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 28 publications
9
118
0
Order By: Relevance
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
“…TAFII28 and RXR ; [2]). In a number of cases there also appears to be specific binding by factors other than TBP to an ' initiator ' motif downstream from the TBP-binding site [3][4][5][6][7][8][9][10][11][12]. There is increasing evidence that particular DNA sequences in the core promoter, other than the TBP-and initiator-binding motifs, play a pivotal role in controlling whether a particular TBP\TAFII complex [13] or other non-TFIID factor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Incubation was carried out at 28°C for 45 min. For primer extension analysis, products of transcription reactions were analyzed by using a primer that hybridized to the chloramphenicol acetyltransferase (CAT) gene (5Ј-CTCCATTTTAGCTTCCTTAG-3Ј) (9). For RNase protection analysis, transcription reactions were stopped by the addition of 2 M ammonium acetate-0.05% sodium dodecyl sulfate-0.05 mM EDTA, extracted with phenol-chloroform, and chloroform and ethanol precipitated.…”
Section: Methodsmentioning
confidence: 99%
“…Gel mobility shift experiments show that a specific, stable complex containing TBP, TFIIB, TFIIF, and highly purified RNAPII can form on the AdMLP, adenovirus IVa2 (AdIVa2), and TdT Inr elements as well as on the TATA-less dihydrofolate reductase (DHFR) promoter (1,9). Template challenge experiments demonstrate that stable preinitiation complex formation on a wide variety of TATA-containing and TATA-less promoters requires TBP, TFIIB, and RNAPII and that TFIID and TFIIF increase and stabilize complex formation.…”
mentioning
confidence: 99%
“…Some genes contain another core element, the initiator, either alone or in addition to a TATA box, which is also able to direct accurate transcription initiation by RNA polymerase II. Several proteins and multiprotein complexes have been reported to be involved in initiator function; these include RNA polymerase II itself (9), transcription factors like E2F (33), YY1 (50), and USF (13), the putative initiator factor TFII-I (46), and the general transcription factor TFIID through its TBP-associated factor components (24,61).…”
mentioning
confidence: 99%